Performing Gender: Nostalgic Wedding Photography in Contemporary China - Huang, Xin (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2006)
By examining gender scripts and performances in Chinese nostalgic studio wedding photography, this article explores the historical and cultural resources available for a particular gender project in contemporary China. It suggests a resonance between the post-Mao gender project and China’s modernity project and Chinese cultural identity construction, and argues that the post-Mao gender project is carried out under the haunting shadow of the Maoist gender ideology, and through cross-cultural negotiations with the Western gaze.